KEBIJAKAN PEMERINTAH DAERAH PULAU JAWA DAN PULAU BALI DALAM MENGHADAPI PANDEMI COVID-19 (Institut Pemerintahan Dalam Negeri, 2021)
This study aims to analyze and explain the policies of the local government of the island of Java and the island of Bali in dealing with Covid-19. Local governments play a significant role in deciding the most appropriate policies for their regions. Local governments are required to carefully identify the problem of handling Covid-19, quickly decide on relevant policies, and ensure that their policies work in dealing with Covid-19 effectively. local governments need to continuously monitor and observe policies for handling COVID-19. Policy improvements regarding the handling of Covid-19 are always required at all times to adapt to the new challenges that are present in the process. In this case, the Regional Governments of Java and Bali Island in preventing Covid-19 have been responsive and responsive. This can be seen when the Central Government instructed local governments, especially Java and Bali islands to carry out handling of Covid-19 such as Large-Scale Social Restrictions (PSBB) and Micro-Scale Social Restrictions (PSBM/PPKM) as well as the implementation of health protocols for wearing masks, washing hands and maintain a minimum distance of 1 meter, each Regional Government issues policies quickly and then socializes them well.Keywords: Local Government, West Java, Covid-19 Pandemi